Skip-beat! 46 - Nakamura, Yoshiki; Kimura, Tomo (Shojo beat manga., 2022)
"Kyoko Mogami followed her true love Sho to Tokyo to support him while he made it big as an idol. But he's casting her out now that he's famous! Kyoko won't suffer in silence--she's going to get her sweet revenge by beating Sho in show biz! Ren Tsuruga loves Kyoko Mogami! It would be the news of the century, but they have to keep it quiet to protect their privacy and their careers. While the happy couple is content to focus on their professional goals for the time being, Ren's legion of fans won't rest until they know what's going on with their fave. Are any secrets safe from these internet detectives?!"--Provided by publisher.